Effect of Incubation of PK-15 Line Cells with Cryoprotectants on Amount of Gal-alpha-1,3-Gal Epitopes - Bohuslavskyi, Konstantin I.; Alabedalkarim, Natalia M.; Pakhomov, Alexsandr V.; Bozhok, Galyna A. (Problems of Cryobiology and Cryomedicine, 2016)
Transplantation of bioprostheses derived from bovine and porcine tissues is an advanced method of correcting defects in blood vessels and valves, however when using it a hyperacute immune response associated with the presence of Gal-alpha- 1,3-Gal (α-Gal epitope) on the surface of cell membranes can develop. We have studied the effect of penetrating and nonpenetrating cryoprotectants on the amount of α-Gal epitopes on membranes of PK-15 cell line of porcine origin. Cell labeling with BSIB4 lectin conjugated with FITC and flow cytometry revealed a significant increase in the number of fluorescent cells after incubation with various concentrations of dimethyl sulfoxide and polyethylene glycol with MW of 1500 (PEG-1500). The revealed effect may be associated with an additional exposure of α-Gal epitopes on cell membrane, locally deformed due to the action of cryoprotectants. Probl Cryobiol Cryomed 2016; 26(4): 331–339